Unexpected Imidazoquinoxalinone Annulation Products in the Photoinitiated Reaction of Substituted-3-Methyl-Quinoxalin-2-Ones with N-Phenylglycine - Aliaga-Silva, C (2013)
Photoinduced electron transfer between N-phenylglycine (NPG) and electronically excited triplets of 7-substituted-3-methyl-quinoxalin-2-ones in acetonitrile generate the respective ion radical pair, where by decarboxylation the phenyl-amino-alkyl radical, PhNHCH2•, is generated. This radical reacts with the 3-methyl-quinoxalin-2-ones ground states, leading to the product 2. Other, unexpected, 7-substituted-1,2,3,3a-tetrahydro-3a-methyl-2- phenylimidazo[1,5-a]quinoxalin-4(5H)-ones, annulation products, 3a-f, were generated; likely by the addition of two PhNHCH2• radicals, to positions 3 and 4 of the quinoxalin-2-ones. The reaction mechanism includes a photoinduced one electron transfer initiation step, propagation steps involving radical intermediates and NPG with radical chain termination steps that lead to the respective products 2a-f and 3a-f and NPG by-products. The proposed mechanism accounts for the strong dependency found for the initial photoconsumption quantum yields on the electron-withdrawing power of the substituent. Therefore, photolysis of common reactants widely used such as NPG and substituted quinoxalin-2-ones may provide a simple synthetic way to the unusual, unreported tetrahydro-imidazoquinoxalinones 3a-f. © 2013 The American Society of Photobiology.